Prospects for creating modern piston compressors with increased performance - S. S. Busarov; K. A. Bakulin; R. E. Kobylskiy; I. S. Busarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The current level of performance of piston compressors, characterized by the delivery coefficient, is at the level of 0,7. Advanced designs have higher rates, reaching values of 0,8...0,85. However, the negative effect of dead volume prevents the performance level of, for example, screw compressors from being achieved. Therefore, reducing the influence of dead volume on productivity can be considered the main task in improving modern piston machines. The presented work proposes a solution to eliminate the influence of the most significant component of the dead volume — linear space. As experimental studies have shown, the use of elastic discs mounted on the piston will virtually eliminate linear dead volume, ensure operational safety and increase the flow rate to 14 %.